Optimization Of A Cutting Process For Wire-Electric Discharge Machining At Welding Joint - F. R. M., Romlay; Asmizam, Mokhtar (2007)
Control system is one of the important applications in automation application. The purpose of the control system in industrial field is to control the flow of the process in part of machine operation. This paper is presented a design for automatic dishwasher utilizing stepper and DC motor control system. The control system in machining process is created by using PLC programmed setup and it is transfer to the higher memory capability chip inside the microcontroller which is microchip ULN2803. The robotic arm, cleaning brush, and water pump which is fully automatic function is totally conducted by the stepper and DC motor.